Inflation, Risk, Taxes, and the Demand for Owner-Occupied Housing - Goodwin, Thomas H. (The Review of Economics and Statistics, 1986)
A bstract-A portfolio choice model is formulated which focuses on the possibility of inflation hedging motives in housing demand in the 1970s. An asset demand equation is used to estimate the capitalization of inflation expectations into house prices through tax, mortgage, and hedging effects. The empirical results indicate that, even after accounting for tax and mortgage effects, the hedging motive was significant in bidding up house prices. One implication is that the tax effects of inflation may have been overstated in previous research that ignored inflation risk.